A pilot study examining the role of regional cerebral oxygen saturation monitoring as a marker of return of spontaneous circulation in shockable (VF/VT) and non-shockable (PEA/Asystole) causes of cardiac arrest - Ahn, Anna; Nasir, Asad; Malik, Hanan; D’Orazi, Francis; Parnia, Sam (Resuscitation, 2013)
Non-invasive monitoring of cerebral perfusion and oxygen delivery during cardiac arrest is not routinely utilized during cardiac arrest resuscitation. The objective of this study was to investigate the feasibility of using cerebral oximetry during cardiac arrest and to determine the relationship between regional cerebral oxygen saturation (rSO2) with return of spontaneous circulation (ROSC) in shockable (VF/VT) and non-shockable (PEA/asystole) types of cardiac arrest. Cerebral oximetry was applied to 50 in-hospital and out-of-hospital cardiac arrest patients. Overall, 52% (n=26) achieved ROSC and 48% (n=24) did not achieve ROSC. There was a significant difference in mean±SD rSO2% in patients who achieved ROSC compared to those who did not (47.2±10.7% vs. 31.7±12.8%, p<0.0001). This difference was observed during asystole (median rSO2 (IQR) ROSC versus no ROSC: 45.0% (35.1–48.8) vs. 24.9% (20.5–32.9), p<0.002) and PEA (50.6% (46.7–57.5) vs. 31.6% (18.8–43.3), p=0.02), but not in the VF/VT subgroup (43.7% (41.1–54.7) vs. 42.8% (34.9–45.0), p=0.63). Furthermore, it was noted that no subjects with a mean rSO2<30% achieved ROSC. Cerebral oximetry may have a role as a real-time, non-invasive predictor of ROSC during cardiac arrest. The main utility of rSO2 in determining ROSC appears to apply to asystole and PEA subgroups of cardiac arrest, rather than VF/VT. This observation may reflect the different physiological factors involved in recovery from PEA/asytole compared to VF/VT. Whereas in VF/VT, successful defibrillation is of prime importance, however in PEA and asytole achieving ROSC is more likely to be related to the quality of oxygen delivery. Furthermore, a persistently low rSO2 <30% in spite of optimal resuscitation methods may indicate futility of resuscitation efforts.